Postoperative hormonal therapy after surgical excision of deep endometriosis. (February 2017) - Somigliana, Edgardo; Busnelli, Andrea; Benaglia, Laura; Viganò, Paola; Leonardi, Marta; Paffoni, Alessio; Vercellini, Paolo
Abstract: The clinical management of women with deep peritoneal endometriosis remains controversial. The debate focuses mainly on the precise role of hormonal medical treatment and surgery and on the most suitable surgical technique to be used. In particular, considering the risks of second-line surgery, prevention of recurrences after first-line surgery is a priority in this context. Post-surgical medical therapy has been advocated to improve the effectiveness of surgery and prevent recurrences. However, adjuvant therapy, i.e. a short course of 3–6 months of hormonal therapy after surgery, has been proven to be of limited or no benefit for endometriosis in general and for deep peritoneal endometriosis in particular. On the other hand, two cohort studies suggest a beneficial effect of prolonged hormonal therapy after surgery for deep endometriosis. Even if this evidence is too weak to confidently advocate systematic administration of prolonged medical therapy after surgery, we argue in favour of this approach because of the strong association of deep endometriosis with other disease forms. In fact, women operated on for deep endometriosis may also face recurrences of endometriomas, superficial peritoneal lesions and pelvic pain in general. The demonstrated high effectiveness of prolonged postoperative therapy for the prevention of endometriomas' formation and dysmenorrhea recurrence should thus receive utmost consideration in the decision-making process.